2021
DOI: 10.33225/jbse/21.20.639
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Information and Communication Technology Engagement Factors on Science Performance Between Singapore and Turkey Using Multi-Group Structural Equation Modeling

Abstract: Information and Communication Technology (ICT) engagement, as a multidimensional construct, plays an increasingly important role in education. The main purpose of this research was to explore the effects of ICT engagement factors on science performance across Singapore and Turkey conditional to the sufficient degree of measurement invariance of ICT engagement scale. The multi-group confirmatory factor analysis results demonstrated strong factorial invariance of ICT engagement scale across Singapore and Turkey,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Starting with the analysis of the results obtained, it was generally observed that the assessment of ICT use and engagement in the educational environment was medium-high. This is in line with other studies [5,[45][46][47][48][49][50]. It is true that certain aspects were below the overall average, as in the case where students forget about time when using electronic devices or where they exchange solutions to problems with digital devices using the Internet.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Starting with the analysis of the results obtained, it was generally observed that the assessment of ICT use and engagement in the educational environment was medium-high. This is in line with other studies [5,[45][46][47][48][49][50]. It is true that certain aspects were below the overall average, as in the case where students forget about time when using electronic devices or where they exchange solutions to problems with digital devices using the Internet.…”
Section: Discussionsupporting
confidence: 91%
“…The main research on the motivation generated by ICT in adolescents is related to education, especially in how the use of ICT in students, at home and at school, influences the performance of reading comprehension [5,45,46], mathematics [47,48] and science [47][48][49][50]. In these three domains or areas of knowledge, there are differences in academic performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the role of teachers in the use of technology in the field of education is very important and great. The teacher's attitude towards technology, his or her efforts to use technology consciously (Stuart et al, 2022), his or her understanding of the nature of technology (Ozkan & Tekeli, 2021), his or her design of technology (Tondeur et al, 2017), questioning what the effects are on the society he or she lives in (Yavuz et al, 2020) and the effective use of technology in education and extracurricular activities (Panisoara et al, 2020) affect students. The main element that adds functionality, spirit and meaning to education and makes it efficient and effective is the teacher (Mashroofa et al,2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on students' performance in science have been conducted using data from TIMSS and PISA (Jiang et al, 2023;Kiliç Depren, 2020;Lay & Chandrasegaran, 2018;Lay & Ng, 2021;Özkan & Tekeli, 2021;Shannag et al, 2013;Tang et al, 2022). Some deal with international comparisons (Aşkın & Öz, 2020;Geske & Kangro, 2002;Lay & Chandrasegaran, 2018).…”
Section: Introductionmentioning
confidence: 99%